Asuransi Dalam Perspektif Syariah - Damisa, Arti (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2016)
Takaful should be based on three principles: the principle of responsible, the principle of mutual help and work together, as well as the principle of protecting each other. Thus, al-ta'min or takaful seen from the perspective of mutual understanding muamalah sharia have to bear the risks against each other, so that one another guarantor and risk of loss. The third principle is basically his form of worship that is tabarru. Mutual bear the risk on the basis of helping each other in goodness with the way each cleanup tabarru or worship funds intended to cover these risks. Willingness "to bear" the risk is essentially a form of mutual help on the basis of kindness to alleviate the suffering of his brother who suffered. In the context of the lives of citizens who provide mutual aid and protection, will manifest a stable social life and peace as the realization of people's awareness to do good that is based on values of faith in God.